Distribution and Sign of Otter Presence Across Rice Fields in 2x11 Kayu Tanam, West Sumatra - Sidik, Muhamad Rayhan; Aadrean, Aadrean; Nurdin, Jabang; Roesma, Dewi Imelda; Usio, Nisikawa (Jurnal Biologi Tropis, 2025)
Otters (subfamily Lutrinae) consist of 13 species distributed worldwide; however, their populations have been steadily declining due to land-use changes and hunting, while information on their presence in the rice fields of 2x11 Kayu Tanam District remains undocumented. This study was conducted with the objective of identifying and document tracks and signs of otter presence in the rice fields of 2x11 Kayu Tanam District. The research was conducted from November 2023 to February 2024 using a field survey method by observing tracks, spraints, and prey remains to determine the distribution of otter signs. Based on the distribution of tracks and signs found, it is suspected that only one species occurs in the area, namely Aonyx cinereus (small-clawed otter). The presence of Aonyx cinereus in the rice fields of 2x11 Kayu Tanam District was confirmed through tracks and other signs of activity. These findings provide a foundation for further research on otter ecology in rice field ecosystems and highlight the importance of conservation efforts to sustain their habitats.